The possible Association of HLA Class II with Bladder Cancer in Iraqi Patients - Al-Khateeb, Shatha M.J.; Al-Darzy, Aida-; Al-Mousawy, Khalida M.; Al-Rubaee, Nasr F.; Ghazala, Shwaqi J. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: - Genetic Factors have a major role in the development of bladder cancer. Objectives: - This study was carried out to shed a light on the possible association of HLA class II antigens and BC patients and to correlate this finding with the family history. Patients and Methodes :- Lymphocytotxicity assay had been used to assess HLAtyping of 65 BC patients and 50 healthy controls. Results:- comparison between BC patients and healthy controls showed several antigens deviations in their frequencies. HLA-DR1, HLA-DQ1 and HLA-DQ3 antigens were observed with increased frequencies in patients group with significant differences (P=0.000, 0.000 and 0.017 respectively). Moreover there was decrease frequency of HLA-DR7 in patients group (P=0.010). Stastical analysis showed non significant correlation of the specific HLA –Ags with family history. Conclusions: - This finding demonstrated that HLA-DR1, DR7, DQ1 and DQ3 might play a role in BC susceptibility. • Department of clinical biochemistry. Collage of Medicine Al-Mustansyriah University • Department of Microbiology. Collage of Medicine. Baghdad University • Ministry of Health.